Evaluate x → 0 lim tan x − cos x + 1 tan x + cos x − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How you be so cool? :P
Log in to reply
Do you not go to school?? (No that's not in rhyme with cool!! : D)..At this time usually Indian students are in schools(1-10th class) {I know it's irrelevant }.......
BTW beauty lies in trigonometry....
Log in to reply
We have been given leave for a month to prepare for Boards and I won't spend the whole month of my (life!) doing Board preparation , do you? :P
Log in to reply
@Nihar Mahajan – That's cool !! ....Yup... Agreed. Boards are useless(With all due respect !!)
As x → 0 , we see that the expression tan x − cos x + 1 tan x + cos x − 1 becomes 0 0 , hence we can use L'Hopital's rule:
x → 0 lim tan x − cos x + 1 tan x + cos x − 1 = x → 0 lim sec 2 x + sin x sec 2 x − sin x = 1 + 0 1 − 0 = 1
Simple standard approach.
Problem Loading...
Note Loading...
Set Loading...
This could well be done in one line by L'hopital but I'll use a pure trigonometric approach. ( U s i n g 1 − cos x = 2 sin 2 2 x , sinx=2 sin 2 x cos 2 x ) tan x − cos x + 1 tan x + cos x − 1 = 2 cos x sin ( x / 2 ) cos ( 2 x ) + 2 sin 2 ( 2 x ) 2 cos x sin ( x / 2 ) cos ( 2 x ) − 2 sin 2 ( 2 x ) = cos x cos ( 2 x ) + sin ( 2 x ) cos x cos ( 2 x ) − sin ( 2 x ) Applying limits, we get: x → 0 lim cos x cos ( 2 x ) + sin ( 2 x ) cos x cos ( 2 x ) − sin ( 2 x ) = 1 + 0 1 − 0 = 1